Shortterm Outcome Air Plombage Thoracoplasty of Empyema Thoracis at Pulmonary Tuberculosis - Muhammad Zulfikar Karim Chan; Brilliant Bergant; Ananda F. Aulia (Rifa'Institute, 2022)
Pulmonary tuberculosis (pulmonary TB) is a type of infectious disease caused by the bacterium Mycobacterium tuberculosis. A male patient aged 40 years, came to the hospital with complaints of shortness of breath, severe shortness of breath for 1 week before coming to the hospital, the patient had a history of having WSD installed, on palpation the left vocal fremitus was stronger than the right, percussion was found to be dim in the basal area. lung, hyperresonance in the medial-apex area pulmo dextra and sonor on pulmo sinistra, decreased vesicular auscultation in the right lung, chest X-ray found pleural effusion. The patient was treated with air surge therapy. After surgery and evaluated for 4 days in the hospital and repeated follow-up on patients where the results of the examination did not find recurrent effusions.